SWOT Analysis on AI-based Self-driving Car Companies - Naveen D. Chandavarkar; Nethravathi P. S. (International Journal of Management, Technology and Social Sciences (IJMTS), 2023)
Purpose: This study examines the challenges and possibilities that advancing self-driving vehicle technologies may provide for transportation regulations. Self-driving technology can benefit low-income households and people with mobility issues since it can increase accessibility while reducing dependability and commuting expenses. This emerging technology has uses and effects that go far beyond any current projections. This study offers a complete review of the relevant papers and literature, covering a range of topics from security to viability from an economic perspective. In this regard, we have analyzed certain parameters on the challenges faced for launching self-driving vehicles. According to the results of the SWOT analysis, a step-by-step strategy to introduce self-driving vehicles is the right approach. The export of self-driving vehicles can help to create jobs and maintain economic stability. Methodology: This study is based on exploratory research by examining various reports from websites and recent research papers. Further, we have accessed and framed Strength-Opportunity (SO), Weakness-Opportunity (WO), Strength-Threat (ST), and Weakness- Threat (WT) strategies for the smooth implementation of self-driving vehicles in India. Finding: The present study will analyze the opportunity in implementing self driving vehicle and factors like exports that will influence Indian economy. Government is rigid with self driving cars because of the fact that many will lose their jobs. Originality: This study addresses a number of concerns, prominent among them is the difficulty in adopting self-driving cars and their effects once they become operational or are made legal. Paper Type: Exploratory based research analysis on challenges for implementation of self driving vehicle.